Effect of indoor air quality on potential risk of obstructive sleep apnea: results from Korea National Health and Nutrition Examination Survey - Sungroul Kim; Birhan Legese Gurmu; Mingi Kim; Chiyou Song; Mee-Ri Lee; Chris Chaeha Lim; Ana M. Rule; Kwang Ik Yang (BMC Public Health)
Abstract Background Using nationally representative data from the 2020–2021 Korea National Health and Nutrition Examination Survey, we examined associations between indoor air pollutant exposure and potential obstructive sleep apnea (OSA) risk, estimated by STOP-BANG questionnaire scores. Methods We included 1,501 participants who completed the STOP-BANG questionnaire and consented to in-home air quality measurements per Korea’s Indoor Air Quality (IAQ) standards. Data were weighted for national representativeness, and multivariate logistic regression models identified determinants of potential OSA risk with adjusted odds ratios and 95% confidence intervals. Results From our adjusted model, odds ratios (95% CI) for OSA risk with a unit increase in age were 1.07 (1.05–1.09) for men and 1.04 (1.01–1.07) for women, respectively. The ratios with systolic blood pressure were 1.05 (1.03–1.06) and 1.01 (0.99–1.02), and those with body mass index (BMI, Kg/m2) were 1.12 (1.01–1.24) and 1.08 (0.95–1.22) respectively. Unit increase in indoor formaldehyde (HCHO) exposure raised OSA risk by 1.02 (1.00–1.02) fold in men, after controlling for socioeconomic and behavioural factors as well as other common indoor pollutants (CO2, PM2.5 and Toluene) and outdoor PM2.5. No significant association was obtained from women’s data. Conclusions Our study found a potential association between elevated indoor HCHO levels and increased OSA risk in men. These findings highlight the importance of indoor air quality in OSA prevention, supporting the future development of more effective prevention models and interventions.